Investigating constructions of masculinity in men's talk of male rape. - Field, Shelley Anne (My University, 2010)
The research investigated how men perceive constructions of masculinity in the talk of male rape. Research on gender relations and masculinities is a growing area of interest. The topic of male rape however, remains underrepresented within this. Male rape draws on discourses of gender, trauma, sex, sexuality and violence. It further offers a controversial topic that participants could engage in to further make sense of the multitude of masculine identities that exist, and how these directly influence responses to gendered phenomena. It is therefore likely to elicit significant constructions of masculinities and hence was used as a vehicle to further add insight into the constructed nature of masculinities. This was achieved through the use of a group of thirteen men who were divided into three focus groups. Each focus group made use of a vignette and a semi-structured interview schedule. Through this method the masculine identities that arose in their talk on male rape were examined. Data were analysed using thematic content analysis in which a social constructionist perspective was applied. It was found that participants strongly adhered to a hegemonic masculine point of reference in discussions. The patriarchal nature of this masculine identity that is subordinating of both women and other masculine identities was consistently used in discussions, thus representing the relatively stable influence of hegemony in gendered relations. Subordinated masculinities emerged more subtly, illustrating a growing acceptance of multiple forms of masculine identities. The results were understood as largely representative of broader society that still elevates the constructed standards of hegemony in conceptualising masculinities. This study thus sheds light on the social constructionist nature evident in society that continually influences the connotations attached to gendered identities within it. The significance in considering the masculine influences in responding to male rape lies in the multiplicity of factors that each involves as these collectively shape society's continued gendered understanding in shaping reality. A topic such as male rape, that directly threatens constructed notions of masculinities, thus allows for a new understanding to emerge in its consideration of the masculine identities that arise in responding to this traumatic experience.
Keywords: Male rape; Trauma; Gender; Identities; Masculinities; Hegemony; Subordination; Patriarchy; Social constructions